EFFECT OF FREQUENT BLOOD DONATIONS ON IRON STORES OF NON ANAEMIC MALE BLOOD DONORS - Badar, Ahmed; Ahmed, Ayesha; Ayub, Muhammad; Ansari, Ahmad Kamal (Journal of Ayub Medical College Abbottabad, 2002)
Background: A healthy blood donor loses about 225 mg of iron per donation. This loss is made up very quickly by mobilizing the iron stores in form of ferritin, followed by replenishing the iron stores if diet is adequate. The situation, however, is different for donors with high frequency of blood donations. Their iron stores are under a constant pressure. In the absence of iron replacement this can lead to emptying of iron stores. We undertook this study to evaluate the effect of frequent blood donations on iron stores of regular male blood donors in Karachi. Methods: This study was carried out at Department of Physiology, BMSI, JPMC, Karachi. Our subjects were 8 groups each with 20 non-anaemic male donors, of 20-40 years age (total=160). The first group was '˜control group' that comprised of first time donors, while the rest 7 groups comprised of donors who had donated 1-7 times in the last two years, the latest being at least 3 months back. The iron stores were measured by determining serum ferritin levels. Results: We found reduction in serum ferritin with increasing frequency of blood donations that became very significant in donors donating 4 or more times in the last two years. Finding of 40% and 50 % iron deficient subjects in the groups donating 6 and 7 times in two years respectively was a surprise for us, as this much high frequency has not been reported from elsewhere. We have tried to justify this extraordinary high frequency with the studies reporting low iron status of Pakistanis and Karachi population. Conclusions: Iron deficiency is very common in regular blood donors of Karachi, there is an immediate need to educate the donors about iron supplementation and yearly ferritin checking of so called '˜super donors'